2014
DOI: 10.1016/s1470-2045(13)70549-7
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel versus active symptom control for refractory oesophagogastric adenocarcinoma (COUGAR-02): an open-label, phase 3 randomised controlled trial

Abstract: Cancer Research UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
379
8
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 527 publications
(417 citation statements)
references
References 26 publications
19
379
8
11
Order By: Relevance
“…The OS time of the TBP group was also equivalent to that of the non-TBP group in the subgroups with HER2 IHC 3+ (median, 11.3 vs. 8 Toxicity. The majority of adverse events associated with chemotherapy (Table II) were grade 1 or 2.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The OS time of the TBP group was also equivalent to that of the non-TBP group in the subgroups with HER2 IHC 3+ (median, 11.3 vs. 8 Toxicity. The majority of adverse events associated with chemotherapy (Table II) were grade 1 or 2.…”
Section: Resultsmentioning
confidence: 83%
“…Compared with the best supportive care, first-line chemotherapy for advanced gastric cancer (AGC) improves survival time and quality of life (2)(3)(4); however, the median overall survival (OS) time is short (9-13 months) (5)(6)(7). Several previous studies have demonstrated that second-line chemotherapy confers a significant survival benefit over best supportive care in AGC, with median OS time ranging from 4 to 9.5 months (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, platinum-based and fluoropyrimidine-based combinations have been established worldwide as first-line regimens for treatment of advanced disease [2]. However, treatment options have been limited after failure of firstline therapy, resulting in short survival [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although cytotoxic agents have formed the backbone of systemic therapies for advanced/metastatic disease for many years [1], it is only recently that a survival advantage for second-line systemic therapy has been demonstrated [2][3][4][5]. Once a survival benefit in patients receiving first-line chemotherapy had been demonstrated for combinations of cytotoxics in the late 1990s [6][7][8], subsequent trials primarily built on this progress by substituting newer cytotoxic agents.…”
mentioning
confidence: 99%
“…A decade after the utility of first-line systemic therapy was established, the oral fluoropyrimidines were introduced into the treatment paradigm for gastric cancer [4,15]. Two large trials established the non-inferiority of capecitabine in comparison with 5-fluorouracil administered by continuous infusion when used in combination with either cisplatin or oxaliplatin.…”
mentioning
confidence: 99%